The Significance of Joseph’s Posthumous Remains in Sir 49:15 - Pudełko, Jolanta Judyta (The Biblical Annals, 2024)
The Praise of the Fathers (Sir 44–49) presents the most outstanding heroes of biblical Israel’s history. The final poem of this praise shatters the historical sequence by returning to the beginning of history. Enoch, Joseph, Shem, Seth (Enos in H) and Adam are mentioned in Sir 49:14–16. The article focuses on presenting the figure of Joseph (49:15) and understanding the significance of mentioning his posthumous remains. The question of the presence and location of this important character in the context of the entire praise and in connection with the other characters of 49:14–16 is first raised. The content of Joseph’s praise in its textual versions (G, H, S) is then analysed, and an attempt is made to interpret their differences. Both the “bones” (49:1 5 G) and the “flesh” (49: 15 H/S) of the patriarch Joseph play an important role in the presentation of this character, indicating his importance in the history of posterity, both in relation to the biblical tradition and comparing Joseph with Alexander the Great.